Application of the porous Volumetric Ceramic Burner for Bread Baking in a Deck Baking Station - Jovicic, Vojislav; Zbogar-Rasic, Ana; Schmitt, Kilian; Luger, Jonas; Delgado, Antonio (Proceedings of 23rd International Symposium, Research-Education-Technology (RET), 2017)

Characterization of the heat transfer within the baking oven based on the volumetric ceramic burner (VCB) technology - Raab, Franziska; Zbogar-Rasic, Ana; Jovicic, Vojislav; Delgado, Antonio (29th EFFoST Conference Proceedings - Food Science Research and Innovation: Delivering sustainable solutions to the global economy and society, 2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.ITC.stmmec.charac

Cleaning of the surfaces in the food industry using cold plasma - Jovicic, Vojislav; Jung, Isabella; Zbogar-Rasic, Ana; Khan, Muhammad Jehanzaib; Delgado, Antonio (Proceedings der 25. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2017)
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.cleani

Combustion of solid fuel in a hybrid porous reactor - Jovicic, Vojislav; Fedorova, Nataliia; Zbogar-Rasic, Ana; Makongue Nloka, Daniel Ernest Gustave; Reichert, Fernando; Delgado, Antonio (Energy Procedia, 2017)
One of the most significant human-made methane emission sources is the municipal solid waste (MSW), deposited on sanitary landfills and open dumps [1,2]. Within this work, an alternative MSW treatment concept is presented, which could provide a relatively clean waste/biomass-to-energy transformation. The proposed procedure comprises of a combustion and a gasification (or pyrolysis) step, which are consecutively taking place in a two-stage hybrid porous reactor system. The core of the system are two packed bed reactors, in which solid fuel (waste or biomass) is mixed with inert ceramic particles of similar size. This paper overviews the initial experimental investigation of the combustion step of a hybrid mixture, composed of wood pellets (fuel) and alumina balls (inert ceramic particles) in a 250 mm-high batch reactor. The temperature profile along the reactor, the concentration of CO and the flame front propagation velocity were measured as a function of the ceramic particle size (11 and 20 mm), the inert-to-fuel mass ratio (0:1, 2:1, 3:1) and the airflow rate (30, 42, 60 l/min). Experiments indicate that an increase of the mass ratio of inert-to-fuel material and a decrease of the inert ceramic particles size lead to a decrease of the maximum temperature of the packed hybrid bed. Measured CO concentrations showed strong dependence on the inert ceramic particle size, i.e. the particle size reduction from 20 to 11 mm resulted in a significant reduction of CO-emission peaks. The maximum flame front propagation velocity of 0.2 mm/sec was detected for the airflow of 42 l/min, the particle size of 20 mm and the mass ratio of 3:1.
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.combus
Keywords: allothermal gasification; Combustion; hybrid filtration combustion; MSW; packed bed

Comparison of the operational characteristics of the commercially available and newly developed porous burner flame traps for high temperature applications - Jovicic, Vojislav; Issendorff, Franz; Kempe, Viktor; Zbogar-Rasic, Ana; Delgado, Antonio (Verbrennung und Feuerung : 27. Deutscher Flammentag, 2015)
UnivIS-Import:2017-11-06:Pub.2015.tech.ITC.stmmec.compar

Degradation of Low Concentrated Perfluorinated Compounds (PFCs) from Water Samples Using Non-Thermal Atmospheric Plasma (NTAP) - Jovicic, Vojislav; Khan, Muhammad Jehanzaib; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Energies, 2018)
Perfluorinated compounds (PFCs) are manmade chemicals, containing the covalent C-F bond, which is among the strongest chemical bonds known to organic chemistry. Abundant use of these chemicals contaminates air, water, and soil around the world. Despite recent initiatives and legal regulations set to reduce their omnipresence, conventional water purification processes are either inefficient or very expensive, especially for low PFC contamination levels. This research is focused on the non-thermal atmospheric plasma (NTAP) decomposition of very low concentrations (<1 µg/L) of PFCs (especially perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS)), present in the wastewater produced during the process of PFCs removal from contaminated soil. The efficiency of the decomposition process was investigated for air, oxygen, and nitrogen plasma, with exposure times of 1–10 min and different plasma nozzle- and reactor sizes. Experiments demonstrated that the NTAP treatment is an efficient alternative method for degradation of more than 50% of the initial PFC concentration in the water samples, in less than 200 s. The final concentration of PFC showed strong dependency on the tested parameters. The treatment effect showed to be strongly non-linear with time, followed by the reduction of the pH-value of the treated sample, which might present a limiting factor for further PFC decompositio
UnivIS-Import:2018-09-11:Pub.2018.tech.ITC.stmmec.degrad
Keywords: Non-thermal atmospheric plasma; Perfluorinated compound (PFC) removal; Wastewater treatment

Development and evaluation of the novel baking concept based on a highly radiative volumetric ceramic burner (VCB) - Jovicic, Vojislav; Zbogar-Rasic, Ana; Takacs, Ronny; Becker, Thomas; Delgado, Antonio (FEI Jahrestagung 2017 - Industrielle Gemeinschaftsforschung als Katalysator des innovativen Mittelstands, 2017)

Development and testing of a new concept for regenerative porous burner with preheated air - Großmann, Katharina; Zbogar-Rasic, Ana; Jovicic, Vojislav; Bauer, Herbert; Delgado, Antonio (Proceedings of the 9th European conference on industrial furnaces and boilers, 2011)
UnivIS-Import:2017-11-06:Pub.2011.tech.ITC.stmmec.develo

Effectiveness of Non-Thermal Plasma Induced Degradation of Per- and Polyfluoroalkyl Substances from Water - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Poser, Alexander; Freichels, Katharina; Delgado, Antonio (Water, 2022)
Per- and polyfluoroalkyl substances (PFAS) are omnipresent synthetic chemicals. Due to their industrial importance and widespread use as a key component in various applications and a variety of products, these compounds can be found today in high concentrations (>1 mu g/L) in surface and groundwater but also spread throughout the ecosystem, where they represent a serious threat to most living organisms. The removal or degradation of PFAS contaminants from water and soil is becoming a legal obligation in a growing number of countries around the globe. This, however, demands novel techniques for the degradation of PFAS since conventional water treatment techniques are either insufficient or extremely expensive due to the persistent nature of these compounds caused by their extraordinary chemical stability. The goal of this work was therefore to investigate the practical potential of the application-oriented use of atmospheric non-thermal plasma as a powerful advanced oxidation method for the purification of water contaminated with PFAS compounds. Special attention was devoted to the development of the concept that can be scaled up to the capacity level of approximately 100-200 m(3) of water per hour, contaminated with PFAS and other contaminants including organic and inorganic material generally present in soil, and surface or groundwater. Our major research interest was to define the minimum required treatment time for optimal purification results, as well as to understand the influence of the initial concentration of PFAS in water and the potential presence of co-contaminants often present in situ on the efficiency of the degradation process. A chemical analysis of the treated samples demonstrated the ability of the atmospheric plasma to reduce more than 50% of the initial PFAS amount in the water samples in less than 300 s of treatment time. PFOA, however, showed more rigidity towards degradation, where a double treatment time was needed to reach similar degradation levels. The obtained results showed that the initial concentration level does not play a major role in the process. However, the PFAS degradation profiles for all tested concentrations show a strongly nonlinear behavior with time, characterized by the fast decrease of the process efficiency in the case of longer treatment times. For prolonged treatment times, a constant increase in the samples' conductivity was measured, which might be the limiting factor for the degradation rate in the case of prolonged treatment times.
CRIS-Team WoS Importer:2022-05-27

Effect of Steam Flow Rate and Storage Period of Superhydrophobic-Coated Surfaces on Condensation Heat Flux and Wettability - Fedorova, Nataliia; Lindner, Christian; Prado, Lucia; Jovicic, Vojislav; Zbogar-Rasic, Ana; Virtanen, Sannakaisa; Delgado, Antonio (Multimodal Technologies and Interaction, 2021)
The jumping-droplet phenomenon occurring on superhydrophobic (SHPhob) surfaces under special conditions may be beneficial for numerous systems using condensation, due to the reported increased heat transfer coefficients. One technique to create a SHPhob surface is coating, which can be applied to larger areas of existing elements. However, challenges are associated with coating stability and the realization of continuous dropwise condensation. This research examined the condensation of steam at different flow rates (2, 4 and 6 g/min) and its influence on heat flux and water contact angles on the SHPhob spray-coated aluminum samples. Special emphasis on the impact of time was addressed through a series of one and five-hour condensation experiments on the samples with different storage periods (coated either one year ago or shortly before testing). Over the experimental series at a higher steam flow rate (6 g/min), heat flux decreased by 20% through the old-coated samples and water contact angles transferred from the superhydrophobic (147°) to hydrophobic (125°) region. This can be attributed to the joint effects of the partial coating washout and the adsorption of the condensed water within the porous structures of the coating during steam condensation. The new-coated samples could sustain more than fifty hours of condensation, keeping the same heat fluxes and SHPhob characteristics.
Keywords: condensation heat transfer; steam flow rate; superhydrophobicity; coating; stability; contact angle

Energieeffizientes Backen mittels innovativer VKB-Technologie: Vom Hartgebäck bis zum Weißbrot - Delgado, Antonio; Jovicic, Vojislav; Zbogar-Rasic, Ana; Becker, Thomas; Geier, Dominik Ulrich; Takacs, Ronny (FEI-Jahrestagung 2017 - Industrielle Gemeinschaftsforschung als Katalysator des innovativen Mittelstands, 2017)

Enhancement of Wheat Flour and Dough Properties by Non-Thermal Plasma Treatment of Wheat Flour - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Applied Sciences, 2022)
Demand to improve food quality attributes without the use of chemicals has risen exponentially in the past few years. Non-thermal plasma (NTP) (also called ‘cold plasma’) is becoming increasingly popular for this purpose due to its unique low-temperature and non-chemical nature. In the present research, the concept of in situ dielectric barrier discharge (DBD) plasma treatment inside a rotational reactor for the direct treatment of wheat flour was experimentally analyzed. The primary research goal was to determine the effects of short-period NTP treatment of DBD type on flour and dough properties. For this purpose, the influence of different operating parameters was tested, i.e., treatment time, the amount of flour placed in the reactor and the environmental (air) temperature. Changes in the structural attributes of the most commonly used flours (type 550 and 1050) and their respective doughs were studied using a set of analytical techniques. Rheological analysis demonstrated the ability of NTP to significantly intensify the visco-elastic properties of dough produced from wheat flour type 550 that was treated for less than 180 s. This indicated that plasma treatment enhanced intermolecular disulphide bonds in gluten proteins, which resulted in stronger protein–starch network formations. However, longer treatment times did not result in a significant increase in the visco-elastic properties of wheat dough. The obtained results showed a 6–7% increase in flour hydration due to NTP treatment, which also makes a contribution to hydrogen bonding due to changes in the bonded and free water phase. Experimental findings further confirmed the dependence of NTP treatment efficiency on environmental air temperature.
CRIS-Team Scopus Importer:2022-09-09
Keywords: dielectric barrier discharge; dough; hydration properties; microstructure; non-thermal plasma; rheology; wheat flour; wheat functionality

Evaluation of baking performance by means of mid-infrared imaging - Takacs, Ronny; Jovicic, Vojislav; Zbogar-Rasic, Ana; Geier, Dominik; Delgado, Antonio; Becker, Thomas (Innovative Food Science & Emerging Technologies, 2020)
The present work aims to validate mid-infrared imaging as a promising method for evaluating oven systems. Therefore, a novel approach by analyzing mid-infrared radiation patterns captured by a thermal camera and subsequent image processing was developed. A thermal camera was adapted to two different oven systems: a standard electric deck oven and a novel gas-fired baking oven with integrated volumetric ceramic burners (VCBs). The baked goods were analyzed and key indicators describing the final product quality were determined. Specific volume, surface browning and mid-infrared image processing demonstrated a comparable performance of both oven systems. Furthermore, the determined surface heat homogeneity of the items to be baked was 0.65 ± 0.05 (–) for the electronic oven and 0.70 ± 0.03 (–) for the VCB oven. The proposed approach proved its fundamental qualification for comparing and evaluating different oven systems.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Baking monitoring; Image processing; Mid-infrared; Oven system evaluation

Experimental and numerical analysis of the heat transfer in a packed bed exposed to the high thermal radiation flux - Ruiz, Gustavo; Ripoll, Nicolás; Fedorova, Nataliia; Zbogar-Rasic, Ana; Jovicic, Vojislav; Delgado, Antonio; Toledo, Mario (International Journal of Heat and Mass Transfer, 2019)
This paper investigates temperature profiles and heat fluxes in a packed bed heated by radiation that simulates solar energy flux. For this purpose, the discrete element method (DEM) was used along a heat transfer model (conduction and radiation mechanism). Short-range model is proposed for considering thermal radiation in a discrete elements system, which represents an easy-to-implement and low-computational-cost alternative. As results of the simulations, thermal profiles through the packed bed were obtained, as well as the accompanying heat flux. Experiments were performed in a packed bed of inert ceramic particles (alumina spheres). A radiant porous burner was placed at the bottom of the packed bed to simulate an imposed concentrated solar heat flux. Numerical results show good agreement with experimental data. In addition, the thermal profiles, obtained by the heat transfer model in DEM, were compared with the results obtained by discretizing the conservation of energy equation of the solid phase using finite differences, showing a correlation between the power and temperatures reached. It is concluded that the radiation model proposed provides the basis to continue with the study of granular materials at high temperature, where radiation is the dominant mechanism</a

Experimental Investigation of Solid Fuel Combustion Process in a Hybrid Porous Reactor - Jovicic, Vojislav; Fedorova, Nataliia; Zbogar-Rasic, Ana; Toledo Torres, Mario; Delgado, Antonio (Journal of Energy and Power Engineering, 2017)
One of the most significant human-made methane emission sources is the MSW (municipal solid waste), deposited on sanitary landfills and open dumps. Within this work, an alternative MSW treatment concept is presented, which could provide a relatively clean waste/biomass-to-energy transformation. The proposed procedure comprises of a combustion and a gasification (or pyrolysis) step, which are consecutively taking place in a two-stage hybrid porous reactor system. The core of the system is two packed bed reactors, in which solid fuel (waste or biomass) is mixed with inert ceramic particles of similar size. This paper overviews the initial experimental investigation of the combustion step of a hybrid mixture, composed of wood pellets (fuel) and alumina balls (inert ceramic particles) in a 250 mm-high batch reactor. The temperature profile along the reactor, the concentration of CO and the flame front propagation velocity were measured as a function of the ceramic particle size (11 and 20 mm), the inert-to-fuel mass ratio (0:1, 2:1, 3:1) and the airflow rate (30, 42, 60 l/min). Experiments indicate that an increase of the mass ratio of inert-to-fuel material and a decrease of the inert ceramic particles size lead to a decrease of the maximum temperature of the packed hybrid bed. Measured CO concentrations showed strong dependence on the inert ceramic particle size, i.e. the particle size reduction from 20 to 11 mm resulted in a significant reduction of CO-emission peaks. The maximum flame front propagation velocity of 0.2 mm/sec was detected for the airflow of 42 l/min, the particle size of 20 mm and the mass ratio of 3:1.
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.experi_8
Keywords: Combustion; allothermal gasification; MSW; hybrid filtration combustion; packed bed

Experimental investigation of the gravity influence on the condensation behaviour on Al and PTFE-samples - Fedorova, Nataliia; Macher, Philipp; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
The condensation heat transfer takes place in numerous industrial processes. The presented work was motivated by the possibility to increase the energy efficiency of industrial processes through the condensation of water vapour from flue gases (FG). It is especially relevant for such industries, like baking, textile, pulp and paper, drying, etc., where the FG at the end of the process is rich in water vapour (up to 90%vol). This FG is generally composed of non-condensable gas (mostly dry air) and condensable gas (mostly water vapour). Its thermal energy (sensible and latent) can be recovered, thus increasing the overall process efficiency. The heat transfer efficiency plays an important role in the condensation process and is strongly influenced by the condensation type. The dropwise condensation exhibits the increased heat transfer coefficient by up to one order of magnitude, comparing to the filmwise condensation. Therefore, the research interest lies in the investigation of methods, prioritizing the dropwise condensation on solid surfaces. One of the decisive mechanisms for the in-creased heat transfer coefficient and condensation rate is the cyclical sequence of droplet formation, growth and drainage. Among others, these are initiated by the surface properties and gravitational force. In order to investigate the influence of gravity on the surface condensation behaviour, the experimental investigation was done for a variable tilt angle of 0, 30, 60 and 75° relative to the horizontal, using two different sample materials (Aluminium and PTFE-Teflon® discs 60 x 3 mm). The reaction chamber was filled with ambient air and kept at 50°C. Simultaneously, the sample was cooled with air and the water vapour was gradually injected inside the chamber. The condensation on the sample was recorded by the HD camera with 180mm macro lens. The pressure and temperature profiles along the reactor were continuously recorded. The condensation process ran two times faster for the inclination angle of 75° compared to 0° in case of the Al-sample. Since the tilt angle induces the natural convection inside the reaction chamber, the vertical temperature gradient decreased with increasing the inclination angle from 0 to 75° (by 40% for the Al-sample; by 20% for the PTFE-sample). Experimental data indicate that gravity reduces the critical droplet size for drainage (from around 4 to 2mm for both samples) and facilitates coalescence effects. This results in an accelerated cycle of nucleation, droplet growth and drainage.
Keywords: Surface condensation; droplet formation; influence of gravity; Aluminium; PTFE (Teflon®)

Impact of non-thermal plasma on the abatement of Perfluorinated compounds present in minute quantities in water effluents - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Based on the strongest C-F bonds backbone, Perfluorinated compounds (PFCs) are manmade chemicals that are omnipresent due to their immense use for the production of various products. Currently, these are also addressed as global contaminants, and are present on the word market since middle of the 20 th century. Non biodegradability and high half-life times generate serious adverse effects on humans and wild life. This calls for remediation. Updated lifetime health advisory, and water quality standards have been issued for PFCs by different US and European environmental agencies, but the conventional techniques for remediation are either inefficient, or turn out to be uneconomic, especially dealing with extremely minute quantities present in effluents. The present study copes with the reduction/removal of low concentrated (<1 μg/l) PFCs from waste water, using non-thermal atmospheric plasma (NTAP). The research experimentally investigates influences of different parameters e.g. plasma gases (air, O2 and N2), treatment times (up to 10 min.) and nozzle/reactor sizes on the reduction of PFC concentrations. Promising results were obtained with NTAP exposure on the PFC concentration levels. In less than 200 seconds, the concentration thresholds of below 50% of initial PFCs concentration was reached in most of the tests within the shown experimental setup. The final concentration of PFCs was strongly dependent on the tested parameters. The decreasing pH value of the water was found to be a limiting factor for the lower PFCs concentration threshol
Keywords: Non-thermal atmospheric plasma; PFC removal; waste water treatment

Influence of Non-Thermal Plasma Treatment on Structural Network Attributes of Wheat Flour and Respective Dough - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Zettel, Viktoria; Delgado, Antonio; Hitzmann, Bernd (Foods, 2023)
Due to its “generally recognized as safe status” (GRAS) and moderate treatment temperatures, non-thermal plasma (NTP) has lately been considered a suitable replacement for chemicals in the modification of food properties and for preserving food quality. One of the promising areas for the application of NTP is the treatment of wheat flour, leading to improved flour properties and product quality and consequently to higher customer satisfaction. In the present research, the German wheat flour type 550, equivalent to all-purpose flour, was treated using NTP in a rotational reactor to determine the influence of short treatment times (≤5 min) on the properties of flour (moisture and fat content, protein, starch, color, microbial activity, and enzymes), dough (visco-elastic properties, starch, wet and dry gluten, and water absorption), and baking products (color, freshness, baked volume, crumb structure, softness, and elasticity). Based on the properties of NTP, it was expected that even very short treatment times would have a significant effect on the flour particles, which could positively affect the quality of the final baking product. Overall, the experimental analysis showed a positive effect of NTP treatment of wheat flour, e.g., decreased water activity value (<0.7), which is known to positively affect flour stability and product shelf life; dough stability increased (>8% after 5 min. treatment); dough extensibility increased (ca. 30% after 3 min treatment); etc. Regarding the baking product, further positive effects were detected, e.g., enhanced product volume (>9%), improved crumb whiteness/decreased crumb yellowness, softening of breadcrumb without a change in elasticity, and limited microorganism and enzymatic activity. Furthermore, no negative effects on the product quality were observed, even though further food quality tests are required. The presented experimental research confirms the overall positive influence of NTP treatment, even for very low treatment times, on wheat flour and its products. The presented findings are significant for the potential implementation of this technique on an industrial level.
CRIS-Team Scopus Importer:2023-06-09
Keywords: cold plasma; dough rheology; hydration; microbial activity; microstructure; protein and starch properties; wheat flour

Influence of the Inter-structural Gap between the Combustion Zone and the Flame Trap on the Properties of the dual Layer Porous Burners in Operation - Jovicic, Vojislav; Friedmann, Eva; Zbogar-Rasic, Ana; Regensburger, Christoph; Delgado, Antonio (Proceedings of the 7th European Combustion Meeting, 2015)
UnivIS-Import:2017-11-06:Pub.2015.tech.ITC.stmmec.influe

Investigation of advanced temperature and thermo shock resistant ceramic components for high temperature porous burners - Jovicic, Vojislav; Zbogar-Rasic, Ana; Kempe, Viktor; Delgado, Antonio; Weiß, Roland; Dannehl, Manfred; Pritzkow, Walter E. C.; Grenz, Reinhard (Proceedings of the 10th European conference on industrial furnace and boilers, 2015)
Expansion of operation range toward higher temperatures is one of the major goals in further development of porous burner technology. This is mostly related to the fact that radiation is the most intensive mechanism of heat transfer from a porous burner to a heated object. Therefore, increase of average temperature generally leads toward higher overall efficiency. In addition, higher average temperatures are opening new possibilities for industrial application of low pollutant porous burner technology. In this study, a series of novel high-performance ceramics in various designs were investigated in short and continuous long-term experiments under different controlled combustion conditions. Materials like fiber-reinforced alumina ceramics, paper-based pre-ceramic materials and wood-based bio-ceramics were successfully characterized. Long-term combustion tests with test time of 100-500 test hours of continuous operation per test, were conducted at near stoichiometric combustion conditions using mixture of natural gas and air. Most of the tested structures and materials was for the first time tested as a porous burner component at this temperature range within the frame of here presented work. Presented results provide significant amount of useful data regarding performances and limitations of investigated novel ceramic materials and structures and also their potential for application as high temperature (1500°C and above) and thermal shock resistant porous burner components like combustion zones, flame traps or burner housing
UnivIS-Import:2017-07-10:Pub.2015.tech.ITC.stmmec.invest

Investigation of the Concepts to Increase the Dew Point Temperature for Thermal Energy Recovery from Flue Gas, Using Aspen® - Fedorova, Nataliia; Aziziyanesfahani, Pegah; Jovicic, Vojislav; Zbogar-Rasic, Ana; Khan, Muhammad Jehanzaib; Delgado, Antonio (Energies, 2019)
Thermal energy of flue gases (FG) dissipating from industrial facilities into the environment, constitute around 20% of the total dissipated thermal energy. Being part of the FG, water vapour carries thermal energy out of the system in the form of the latent heat, which can be recovered by condensation, thus increasing the overall efficiency of an industrial process. The limiting factor in this case is the low dew point temperature (usually 40–60 °C) of the water vapour in the FG. The increase of the dew point temperature can be achieved by increasing the water content or pressure. Taking these measures as a basis, the presented work investigated the following concepts for increasing the dew point temperature: humidification of the flue gas using water, humidification using steam, compression of the FG and usage of the steam ejector. Modelling of these concepts was performed using the commercial software Aspen®. The humidification of the FG using water resulted in the negligible increase in the dew point (3 °C). Using steam humidification the temperatures of up to 92 °C were reached, while the use of steam ejector led to few degrees higher dew point temperatures. However, both concepts proved to be energy demanding, due to the energy requirements for the steam generation. The FG compression enabled the achievement of a 97 °C dew point temperature, being both energy-efficient and exhibiting the lowest energy cos
Keywords: thermal energy recovery; flue gas; dew point temperature; condensation; Aspen®

Investigation of velocity distribution over a perforated burner plate - Zbogar-Rasic, Ana; Altendorfner, Mirjam; Steven, Martin; Trimis, Dimosthenis; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.invest_4

Mehr Effizienz - Volumetrische keramische Brenner - eine innovative, energieeffiziente Technologie für den Backprozess - Takacs, Ronny; Geier, Dominik Ulrich; Becker, Thomas; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Backtechnik Europe, 2017)
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.mehref

New oven concept with dominant near-infrared (NIR) thermal radiation heat transfer - Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Cereal Technology [Getreidetechnologie], 2019)

Numerical analysis of heat transfer characteristics in energy piles - Zhou, Long; Masood, Rao Muhammad Atif; Jovicic, Vojislav; Zbogar-Rasic, Ana; Kempe, Viktor; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2017-12-18:Pub.2014.tech.ITC.stmmec.numeri_69

Optimization of Fuel Inlet Configuration for Porous Burners with Preheated Air - Großmann, Katharina; Zbogar-Rasic, Ana; Jovicic, Vojislav; Delgado, Antonio; Bauer, Herbert (Proceedings of the European Combustion Meeting 2011, 2011)
UnivIS-Import:2017-11-06:Pub.2011.tech.ITC.stmmec.optimi_8

Optimization of inlet mixture quality by means of third gas for regenerative porous burners with highly preheated air - Zbogar-Rasic, Ana; Großmann, Katharina; Nienhaus, Christoph; Jovicic, Vojislav; Bauer, Herbert; Delgado, Antonio (Proceedings of the 6th European Combustion Meeting (ECM 6), 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.optimi

Overview of experimental evaluation of innovative non-thermal plasma treatment of biotic and abiotic matter - Jovicic, Vojislav; Zbogar-Rasic, Ana; Groß, Frauke; Jung, Isabella; Seok, Julie; Kim, Yoonjin; Delgado, Antonio (Proceedings of the International Nonthermal Processing Workshop, 2015)
UnivIS-Import:2017-11-06:Pub.2015.tech.ITC.stmmec.overvi

Role of Individual Heat Transfer Mechanisms Within a Model Baking Oven Heated by Porous Volumetric Ceramic Burners - Jovicic, Vojislav; Zbogar-Rasic, Ana; Burjakow, Benedikt; Delgado, Antonio (Frontiers in Chemistry, 2020)
The baking process demands a high amount of energy, but only one-third of the total energy supply to the baking oven is actually used for baking, while the rest is dissipated to the environment. This implies that the energy input to the baking process can be significantly reduced, e.g., by enabling a more efficient heat transfer to the product, compared to commercially available ovens. Application of highly radiative, gas-fired heat sources, with a wide power modulation range, such as porous volumetric ceramic burners (VCB), can lead to a reduction in both the baking time and the energy input to a baking oven. In order to optimize energy input to a wide variety of baking products, the role of individual mechanisms in heat transfer between a heat source and a baking product needs to be determined. In the scope of this work, the analysis of the heat transfer within a baking oven model, heated by porous VCBs, was conducted. Contribution of heat transfer mechanisms (heat conduction, convection, thermal radiation) to the total heat transfer was determined by the difference method, where two aluminum cubes of different surface characteristics were used as target objects. Further, the influence of water, commonly added to the baking chamber in form of steam or aerosol, on the heat transfer characteristics within the oven was investigated. Without water addition, the heat transfer between the porous VCBs and the test object occurred mainly through thermal radiation ( 45%), followed by heat conduction and convection ( 27.5% each). Compared to the reference, commercially available electrical deck baking oven, the share of thermal radiation in the model oven was increased (+ 10%), whereas the share of heat conduction was reduced (−20%). With water addition, the heat transfer to the test object through heat conduction, convection, and thermal radiation declined, as an additional heat transfer through condensation took place. Results of this research provide necessary understanding of the heat transfer mechanisms within the novel baking oven, heated by porous VCBs. They are the base for optimization of the heat transfer from the VCBs to different baking goods, through changing the VCB's operating parameters.
CRIS-Team Scopus Importer:2020-11-06
Keywords: baking oven; combustion in porous inert media; infrared baking; porous media burner; thermal radiation

Spektroskopische Untersuchung und Charakterisierung der Nah-Infrarot (NIR) Strahlung eines volumetrischen keramischen Porenbrenners - Jovicic, Vojislav; Nienhaus, Christoph; Zbogar-Rasic, Ana; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.spektr

Static wettability of differently mechanically treated and amphiphobic-coated aluminium surfaces - Fedorova, Nataliia; Ottinger, Bettina; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio; Virtanen, Sannakaisa (Materials, 2020)
Wettability, roughness and surface treatmentmethods are essential for themajority of practical applications, where liquid-solid surface interactions take place. The present study experimentally investigated the influence of different mechanical surface treatment methods on the static wettability of uncoated and amphiphobic-coated aluminium alloy (AlMg3) samples, specially focusing on the interaction between surface finishing and coating. Five different surfaces were prepared: as-received substrate, polished, sandpapered, fleece-abraded and sandblasted. After characterisation, the samples were spray-coated using an amphiphobic coating. The characterisation of the uncoated and coated samples involved measurements of the roughness parameters and the apparent contact angles of demineralized water and rapeseed oil. The coating was initially characterised regarding its adhesion to the sample and elevated temperature stability. The applied surface treatments resulted in the scattered sample roughness in the range of Sa = 0.3-15.8 μm, water contact angles of θap,w = 78°-106° and extremely low oil contact angles. Coating the samples more than doubled the surface roughness to Sa = 13.3-29 μm, whereas the initial surface treatment properties (structure, anisotropy, etc.) were entirely repressed by the coating properties. Coating led the water contact angles to increase to θap,w_coated = 162°-173° and even more pronounced oil contact angles to increase to θap,o_coated = 139°-150°, classifying the surfaces as superhydrophobic and oleophobic.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Amphiphobic; Contact angle; Roughness; Superhydrophobic; Surface treatment; Wettability

Syngas production from waste tires using a hybrid filtration reactor under different gasifier agents - Toledo Torres, Mario; Ripoll, Nicolás; Céspedes, José; Zbogar-Rasic, Ana; Fedorova, Nataliia; Jovicic, Vojislav; Delgado, Antonio (Energy Conversion and Management, 2018)
This paper investigates the syngas production in a hybrid filtration reactor composed of aleatory waste tires particles and alumina spheres. Parameters as reaction wave temperature, propagation rate and gaseous and solid emissions products were measured as a function of gasifier agents (air and steam) and natural gas presence. Hydrogen and carbon monoxide concentrations in the reaction products were determined by gas chromatography and solid emissions by X-ray spectrometry. Downstream reaction zone propagation was observed in all experiments yielding high reaction temperature (1,100–1,500 K) responsible of: (1) generating H2 and CO as main products of the process for different gasifier agents and natural gas presence, and (2) decreased solid particles emissions in comparison with temperatures below 1,100 K. X-ray spectrometry with total reflection was able to detect peaks of Zn and Fe, thought to originate from waste tires particles as well as from reactoŕs insulation material. It was detected that pure air had the best performance as a gasifier agen
Keywords: Hydrogen; Hybrid filtration reactor; Tires valorization; Solid emissions

Virtual engineering as a base for the novel deck baking oven design - Jovicic, Vojislav; Zbogar-Rasic, Ana; Luger, Jonas; Delgado, Antonio (32nd International Conference of European Federation of Food Science and Technology, 2018)